The overnighters [videorecording (DVD)] - Moss, Jesse; Moss, Jesse; Reinke, Jay, 1956-; Edwards, Keegan (Drafthouse Films (Series), 2014)
An intimate portrait of job-seekers desperately chasing the broken American Dream to the tiny oil boom town of Williston, North Dakota. With the town lacking the infrastructure to house the overflow of migrants, pastor Jay Reinke starts the controversial 'overnighters' program, allowing down-and-out workers a place to sleep at the church. His well-meaning project immediately runs into resistance with his community, forcing the clergyman to make a decision which leads to profound consequences.